Pengaruh Eco Literacy Terhadap Green Economy - Amin Setiyadi; Nasrudin Nasrudin; Syamsul Hilal (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by excessive exploitation of nature which results in climate change and reduces the productivity of agricultural products. The purpose of this study was to analyze the effect of eco literacy on the green economy with SDGs as a moderating variable for farmers in Sumber Baru Village. The method in this research is quantitative research. The data used is primary data obtained from Sumber Baru Village farmers in 2022 through observation, interviews and questionnaires. Using a purposive sampling technique so that the research sample is 90 research samples. The collected data were analyzed using multiple linear regression. The test equipment used was IBM SPSS 22. This study shows that simultaneously eco literacy has a significant influence on the green economy with the SDGs as a moderating variable with a significance of 0.000. The results of the partial test show that eco literacy has a significant effect on the green economy with the SDGs as a moderating variable with a significance value of 0.000. The adjusted R2 coefficient of determination is 0.771 or 77%. This means that the ability of eco literacy with the SDGs as a moderating variable has a strong influence on the green economy and 23% is influenced by other variables outside the model which are not the focus of research in this thesis. The conclusion in this study shows that eco literacy has an effect on the green economy with the SDGs as a moderating variable. In line with this research, it is suggested to the agricultural office to be more active in conducting outreach and counseling to farmers regarding the importance of increasing eco literacy, understanding SDGs so as to realize a green economy. It is suggested to farmers as the vanguard in agriculture to strengthen eco literacy and practice SDGs to create a green economy.